Peran Mahasiswa dalam Membentuk Karakter Pelajar Pancasila Melalui Pengabdian Masyarakat Berbasis Lingkungan: Analisis Efektivitas dan Tantangan - Wajdi, Farid; Waris, Andi Ayuni; Wahyu, Jumiani; Sartika, Sartika; Febrianti, Amalia Anggita; Syafira, Nur Aini; Fitriani, Fitriani; Zalzah, Aqyllah; Damayanti, Alya; Karni, Karni; Gunawan, Untung; Adnan, Muhammad; Ramadhan, Agung Gema (Universitas Negeri Makassar, 2025)
Character building based on Pancasila values is important as a foundation for creating a young generation that is not only academically intelligent but also has strong moral integrity, ethics, and social awareness. This character education is not only a supplement but is the core of developing a complete and quality Indonesian human resource. Community service aims to apply Pancasila values to elementary school students through environment-based education. The implementation of community service is carried out in elementary schools in Pelambua Village, Pomalaa District, and Kolaka Regency, namely SDN 1 Pelambua, SLB Negeri 2 Kolaka, and the local community. The implementation period is from July 14 to August 23, 2025. The implementation method uses a qualitative case study. The community service program implemented by students includes education on gadget use, education on violence and sexual thoughts, anti-bullying education, education on healthy living, education on love-pride-and-understanding the rupiah, motivational education through a lively Indonesian Independence Day competition, education on waste resilience, education on family medicinal plant cultivation, and counseling on pest and pesticide control. Evaluation of community service results shows the understanding and skills of students and the community in carrying out daily activities based on Pancasila values, such as participating in religious activities, protecting the environment, cultivating a healthy lifestyle, and other activities that reflect Pancasila character values.